2016
DOI: 10.4238/gmr.15037668
|View full text |Cite
|
Sign up to set email alerts
|

Role of GSTM1, GSTT1, and GSTP1 IIe105Val gene polymorphisms in the response to chemotherapy and overall survival of advanced non-small cell lung cancer

Abstract: ABSTRACT. We evaluated the association between GSTM1, GSTT1, and GSTP1 IIe105Val gene polymorphisms and treatment outcomes of advanced non-small cell lung carcinoma. Between January 2010 and December 2012, a total of 244 patients with non-small cell lung carcinoma were recruited from Yiwu Central Hospital. The GSTM1, GSTT1, and GSTP1 IIe105Val gene polymorphisms were analyzed by polymerase chain reaction-restriction fragment length polymorphism and the results were statistically analyzed. Conditional regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…After carefully screening the titles and abstracts, 121 studies were excluded. Finally, 23 studies met the study selection criteria for meta-analysis [ 2 , 3 , 7 – 16 , 19 – 21 , 23 – 30 ] ( Figure 1 ). Among the 23 studies, there were eight studies of non-small cell lung cancer (NSCLC) with 640 cases and 928 controls for the GSTM1 null genotype, six studies with 518 cases and 822 controls for the GSTT1 null genotype, 23 studies including 1733 cases and 1374 controls for the GSTP1 IIe105Val genotype.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After carefully screening the titles and abstracts, 121 studies were excluded. Finally, 23 studies met the study selection criteria for meta-analysis [ 2 , 3 , 7 – 16 , 19 – 21 , 23 – 30 ] ( Figure 1 ). Among the 23 studies, there were eight studies of non-small cell lung cancer (NSCLC) with 640 cases and 928 controls for the GSTM1 null genotype, six studies with 518 cases and 822 controls for the GSTT1 null genotype, 23 studies including 1733 cases and 1374 controls for the GSTP1 IIe105Val genotype.…”
Section: Resultsmentioning
confidence: 99%
“…These studies contained two subgroups with 20 studies including patients from East-Asia and three studies that included Caucasian patients with NSCLC. The essential information of the included 23 publications are shown in Tables 1 – 5 [ 2 , 3 , 7 – 16 , 19 – 21 , 23 – 30 ]. Three individuals reviewed the studies to avoid potential bias in data interpretation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reviewed studies show that GSTM1 deletion appears to have no effect or could imply a slightly shorter survival. Three studies showed better survival for null GSTM1 (12,13,27) but only 2 of them had statistically significant results (12,13). Regarding GSTT1 deletion, most of the studies found no effect or a tendency to present a worse survival for individuals with the gene absent.…”
Section: Discussionmentioning
confidence: 99%
“…II). Some studies showed positive results in overall survival related to GSTM1 deletion (12,13,27), and 2 of them (12, 13) showed significant results through improving the response to chemotherapy. Median survival was 2.82 months longer for GSTM1-null patients (13).…”
Section: Overall Survival Related To Gstm1 Deletionmentioning
confidence: 99%